2010
DOI: 10.1542/peds.2009-3284
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pain During Two Methods of Urine Collection in Preterm Infants

Abstract: SPA was more painful than UC, as assessed by brow-bulging, and had a tendency to be associated with a higher rate of procedure failure. These findings should be taken into consideration when choosing between these 2 procedures for preterm infants who undergo urine sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…In the previous technical report, SPA was reported to have success rates ranging from 23% to 90%, 22-24 although higher success rates have been achieved when SPA is conducted under ultrasonographic guidance. 25,26 SPA is considered more invasive than catheterization and, in RCTs from 2006 27 and 2010, 28 pain scores associated with SPA were significantly higher than those associated with catheterization. This result was found for both boys and girls.…”
Section: Obtaining a Urine Samplementioning
confidence: 97%
See 1 more Smart Citation
“…In the previous technical report, SPA was reported to have success rates ranging from 23% to 90%, 22-24 although higher success rates have been achieved when SPA is conducted under ultrasonographic guidance. 25,26 SPA is considered more invasive than catheterization and, in RCTs from 2006 27 and 2010, 28 pain scores associated with SPA were significantly higher than those associated with catheterization. This result was found for both boys and girls.…”
Section: Obtaining a Urine Samplementioning
confidence: 97%
“…Similar to previous studies, these RCTs also revealed lower success rates for SPA (66% and 60%), compared with catheterization (83% and 78%). 27,28 In comparison with SPA results, cultures of urine specimens obtained through catheterization are 95% sensitive and 99% specific. 7,11,12 Cultures of bag specimens are difficult to interpret.…”
Section: Obtaining a Urine Samplementioning
confidence: 99%
“…Moreover, both methods are associated with pain and discomfort for both the child and caregivers [40].…”
Section: Collection Of Urine Samples For Microbiological Diagnosismentioning
confidence: 99%
“…We considered a between-group difference of 20% in facial grimacing scores to be a minimal clinically important difference. 37 Assuming an SD of 35%, 65 participants per group were required to detect a 20% between-group difference at the 5% 2-sided level of significance with 90% power. 38 Data were analyzed by using the SPSS statistical software package (version 21; IBM SPSS Statistics, IBM Corporation, Chicago, IL).…”
Section: Discussionmentioning
confidence: 99%
“…27,[32][33][34][35][36][37] These 3 actions have been found to be most frequently associated with tissue damage and exhibit high interobserver reliability, 26 internal consistency, contribute most heavily to the pain experience, 32,33 and are associated with improved specificity without compromising sensitivity or validity. 35 Using a previously described approach, 37 the presence or absence of a facial action was scored for 2-second intervals for each video segment by 2 independent outcome assessors blinded to study hypothesis and group assignment. The percentage of time the facial action was present was calculated for each 30-second segment by dividing the sum of the number of times the facial action was observed in each 2-second interval by the total number of intervals observed, and multiplying by 100.…”
Section: Outcome Measuresmentioning
confidence: 99%